Assessing Psycho-Social Resilience in Diplomatic, Civilian & Military Personnel Serving in a High-Threat Security Environment during Counter-Insurgency and Counter-Terrorism Operations in Iraq - Anne Speckhard; Gino Verleye; Beatrice Jacuch (Perspectives on Terrorism)
Currently thousands of military, diplomatic and civilian personnel are deployed under NATO, UN, and other multi-national, as well as national auspices in high-threat security environments, including active conflict zones such as Iraq and Afghanistan.  Soldiers are generally well trained and prepared psychologically to face armed conflict. Civilian contractors and diplomats, on the other hand, often are not.  Moreover in today’s high-threat security environments terrorists, insurgents and even child soldiers may be the opposing force, creating a more uncertain and anxiety provoking environment and more difficult to identify security threat. These facts have serious implications for the psycho-social resilience of diplomatic, civilian and military personnel deployed in such environments.  This article investigates psycho-social resilience in a small exploratory sample of US embassy staff, contractors and US forces serving in Iraq during 2007, a time when Improvised Explosive Devices (IEDs), roadside bombings, mortar attacks, kidnappings, murders and sniper fire were an everyday occurrence in Iraq.